Intestine-specific Mttp deletion decreases mortality and prevents sepsis-induced intestinal injury in a murine model of Pseudomonas aeruginosa pneumonia. - Jessica A Dominguez (Public Library of Science (PLoS), 2012)
Background The small intestine plays a crucial role in the pathophysiology of sepsis and has been referred to as the "motor" of the systemic inflammatory response. One proposed mechanism is that toxic gut-derived lipid factors, transported in mesenteric lymph, induce systemic injury and distant organ failure. However, the pathways involved are yet to be defined and the role of intestinal chylomicron assembly and secretion in transporting these lipid factors is unknown. Here we studied the outcome of sepsis in mice with conditional, intestine-specific deletion of microsomal triglyceride transfer protein (Mttp-IKO), which exhibit a block in chylomicron assembly together with lipid malabsorption. Methodology/principal findings Mttp-IKO mice and controls underwent intratracheal injection with either Pseudomonas aeruginosa or sterile saline. Mttp-IKO mice exhibited decreased seven-day mortality, with 0/20 (0%) dying compared to 5/17 (29%) control mice (p<0.05). This survival advantage in Mttp-IKO mice, however, was not associated with improvements in pulmonary bacterial clearance or neutrophil infiltration. Rather, Mttp-IKO mice exhibited protection against sepsis-associated decreases in villus length and intestinal proliferation and were also protected against increased intestinal apoptosis, both central features in control septic mice. Serum IL-6 levels, a major predictor of mortality in human and mouse models of sepsis, were elevated 8-fold in septic control mice but remained unaltered in septic Mttp-IKO mice. Serum high density lipoprotein (HDL) levels were reduced in septic control mice but were increased in septic Mttp-IKO mice. The decreased levels of HDL were associated with decreased hepatic expression of apolipoprotein A1 in septic control mice. Conclusions/significance These studies suggest that strategies directed at blocking intestinal chylomicron secretion may attenuate the progression and improve the outcome of sepsis through effects mediated by metabolic and physiological adaptations in both intestinal and hepatic lipid flux.